Intermediate hosts with genetic resistance to Fasciola hepatica and preliminary evaluation of its use in the control of fasciolosis in cattle in the Cajamarca Area, Perú - Cabrera–González, Marco; Hobán, Cristian; Quilcate–Pairazamán, Carlos; Cueva–Rodríguez, Medali (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
With the objective of preliminarily evaluating populations of morphotypes with patterns of phenotypic markers of resistance to artificial infection by miracidium for their use in the control of fasciolosis in cattle, intermediate hosts with resistance to infective forms of Fasciola hepatica were multiplied under conditions laboratory, 850 snails were collected from the ditches and swampy areas of 8 herds located in the districts of La Encañada and Baños del Inca, Peru, located at an altitude of 2,626 to 3,115 meters above sea level (msnm), of the genus Lymnaea viatrix, selecting 400 snails with patterns of susceptibility/resistance to artificial infection by miracidium (shell morphometry, oviposition behavior, mantle pigmentation pattern). Two breeding methods of multiplication of morphotypes were tested, observing that breeding method 1 obtained a lower average mortality of n=11 ± 2.44 in relation to method 2, in terms of fecundity it was higher in method 1 (n=8) in relation to method 2 (n=3); The viability of the egg masses in method 1 was 60% and in method 2 was 48.4%. The incubation time of the eggs was 19 days at 18°C. The resistance found and observed of these morphotypes evaluated the preliminary resistance against miracidium in laboratory conditions, observing that it was 5% in the genus Lymnaea and can be extrapolated to field conditions, taking into account the observations made regarding adaptability, population density, adaptability and survival during the time of year and the parasite load can be used as an alternative control to the inadequate chemical control that causes the resistance phenomenon of F. hepatica.